AI-powered search - Grainger, Trey (Manning Publications, 2025)
AI-Powered Search teaches you to create a search that understands natural language and improves automatically the more it is used. As you work through dozens of interesting and relevant examples, you'll learn powerful AI-based techniques like semantic search on embeddings, question answering powered by LLMs, real-time personalization, and Retrieval Augmented Generation (RAG).
Online resource; title from title details screen (O'Reilly, viewed April 9, 2025)
Keywords: Web search engines; Artificial intelligence; Natural language processing (Computer science); Moteurs de recherche sur Internet; Intelligence artificielle; Traitement automatique des langues naturelles; artificial intelligence; Audiobooks; Livres audio